A survey on define daily dose of watch- and access-category antibiotics in two Indonesian hospitals following the implementation of digital antimicrobial stewardship tool - Ronald Irwanto Natadidjaja; Aziza Ariyani; Hadianti Adlani; Raymond Adianto; Iin Indah Pertiwi; Grace Nerry Legoh; Alvin Lekonardo Rantung; Hadi Sumarsono (Clinical eHealth)
Background: In 2023, the World Health Organization (WHO) began targeting a shift in antibiotic prescribing trends from Watch to Access category. The expected target is including 60% of antibiotic prescribing in the Access category. Method: This survey was a preliminary study, in which our study group designed a digital model of antimicrobial stewardship and the model was known as e-RASPRO. It was an initial review on the implementation of e-RASPRO tool prior to its wider use in future hospitals. The survey on the use of antibiotic Define Daily Dose / 100 patient days (DDD) was carried out in two hospitals in Indonesia at 3 months and 9 months of use, respectively. Hospital 1 as a primary hospital, Hospital 2 as a referral hospital. Data was retrieved retrospectively at the inpatient wards of both hospitals. Result: Three months before and after the implementation of e-RASPRO in Hospital 1, we found an increase in DDD of prophylactic antibiotic Cefazolin by 167.18 %. In hospital 2, it could not be described because Cefazolin had been used since the hospital applied the manual RASPRO concept. DDD of Watch category antibiotics within 9 months following the implementation of e-RASPRO tool in hospital 1 showed a decrease of 49.01 %. Meanwhile, the implementation of e-RASPRO for 3 months in Hospital 2 still showed an increase in Watch category antibiotics by 20.18 %; however, there was a decrease in DDD of Cephalosporin and Glycopeptide antibiotics by 7.63 % and 49.30 %, respectively. In the meantime, as a way of saving antibiotic use and shifting antibiotic prescribing to the Access category, we found a decrease in DDD of Access category antibiotics in Hospital 1 by 3.64 % and an increase in Hospital 2 by 8.14 % Conclusion: The survey may indicate that there are savings attempts in antibiotic use as well as an early change in DDD antibiotics from the Watch category to the Access category following the implementation of e-RASPRO tool in both hospitals. The time period of using the digital devices may still affect the results; however, this survey certainly has not illustrated a strong cause-and-effect correlation between the use of e-RASPRO tool and antibiotic DDD.